2023
DOI: 10.21741/9781644902417-30
|View full text |Cite
|
Sign up to set email alerts
|

On the utilization of radial extrusion to characterize fracture forming limits. Part II: testing and modelling

Abstract: Abstract. This second part of the paper is focused on double-action radial extrusion testing and modelling to characterize material formability and failure in the bulk-to-sheet material flow transitions that are commonly found in metal forming. Results show that three-dimensional to plane-stress evolutions at the radially extruded flanges lead to different modes of fracture (by tension and by shear) that may or may not be preceded by necking. The use of double-action radial extrusion as a formability test also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…This overcomes the difficulty of obtaining Under these circumstances, the main objective of this paper is to investigate formability in three-dimensional to plane-stress material flow transitions by means of a new formability test based on the working principle of double-action radial extrusion [16] on both wrought and additively manufactured aluminum alloys. The paper is an extension of previous work of the authors in wrought aluminum alloys [17,18] and, as will be shown, depending on the aspect ratio and overall ductility of the specimens, the diameter-to-thickness ratio of the radially extruded flange may reach typical plane stress values. This allows analyzing strain path evolutions and failures in three-dimensional to plane-stress material flow transitions by means of digital image correlation (DIC), scanning electron microscopy (SEM), and finite element modeling.…”
Section: Introductionmentioning
confidence: 64%
“…This overcomes the difficulty of obtaining Under these circumstances, the main objective of this paper is to investigate formability in three-dimensional to plane-stress material flow transitions by means of a new formability test based on the working principle of double-action radial extrusion [16] on both wrought and additively manufactured aluminum alloys. The paper is an extension of previous work of the authors in wrought aluminum alloys [17,18] and, as will be shown, depending on the aspect ratio and overall ductility of the specimens, the diameter-to-thickness ratio of the radially extruded flange may reach typical plane stress values. This allows analyzing strain path evolutions and failures in three-dimensional to plane-stress material flow transitions by means of digital image correlation (DIC), scanning electron microscopy (SEM), and finite element modeling.…”
Section: Introductionmentioning
confidence: 64%